Firm’s Characteristics as Predictors of Corporate Failure: Evidence from UK Companies using Logistic Regression - Hu, Cheng (2012)
Analysis of credit risk and increased competition in financial market has improved the motivation of a prediction model of corporate failure. However, there are fewer researches dependent on UK companies. This paper builds up a prediction model of corporate by investigating firm’s characteristics. These characteristics include financial ratios and firm’s size. All financial data used in this study is collected from UK manufacturing companies over five years from 2003 to 2007. Based on the empirical findings of logistic regression, probability ratios, liquidity ratios and firm’s size are estimated to have significant impacts on prediction of corporate failure. In fact, if there are increases of these ratios, the probability of corporate failure will decrease. The predictive power of this logistic analysis is high though there are some limitations.